Simbol, Status, dan Spiritualitas: Makna Sosial Tradisi Batamat Al-Qur'an pada Generasi Muda Banjar - Zaskia Najwa Azzahra; siti afifah (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The Batamat Al-Qur’an tradition in Banjar society remains alive as a religious and cultural expression, yet among young people its meaning is shifting because of modernization and digital media. Previous studies have mostly discussed Batamat in terms of culture, education, and continuity, while research linking symbolism, social status, and the spirituality of Banjar youth remains limited. This study formulates questions on the general form of Batamat, its symbolic meaning, its function as a marker of social status, and youth spirituality, with the aim of explaining these four aspects concretely. Data were collected through library research on journals, books, and scholarly documents published in 2020–2026, then processed through data reduction, classification, interpretation, and descriptive-analytical analysis. The findings show that Batamat functions as a communal rite marking Qur’anic completion, a symbol of religious achievement, respect for teachers and parents, a medium of family honor, and a means of cultivating gratitude, adab, and closeness to the Qur’an. Therefore, Batamat Al-Qur’an remains relevant for Banjar youth as a form of cultural Islam that integrates cultural identity, social legitimacy, and spiritual strengthening.